EVALUASI PENATALAKSANAAN IRIGASI KANDUNG KEMIH KARENA RETENSI BEKUAN DARAH PADA PASIEN GANGGUAN PERKEMIHAN : SYSTEMATIC REVIEW - M Alfian Rajab; Elly L Sjattar; Abdul Majid; Risnah Risnah (Universitas Islam Negeri Alauddin Makassar, 2020)
Clot retention is a common urological condition, if clot retention is left untreated, it can lead to severe pain, tachycardia, hypertension and bladder rupture, the most common cause of which is post-transurethral resection of the prostate (TURP). Thus, bladder irrigation is used to prevent obstruction, bleeding and clots that may occur after TURP surgery, and to maintain patency of the urinary catheter. Therefore, it is this systematic aim to evaluate the management of bladder irrigation due to clot retention in patients with urinary disorders. The research design was systematic reveiw based on PRISMA and question formulation using PICOT. The electronic databases used are Pubmed, Scincedirect, Proquest, Wiley and Google Scholar. With research inclusion criteria in accordance with research objectives, English, published in the last 10 years from 2010-2020 and full text. There were 6 articles reviewed, namely 2 articles with the cohort study method and 4 articles with the clinical trial / experimental study method. This systematic review shows that the Manual Bladder Washout (MBW) procedure is the main choice in the treatment of frequent blood clot retention, but there are various new alternative options such as the